Numerical Simulation of Rock Plate Cutting with Three Sides Fixed and One Side Free - Zhenguo Lu; Lirong Wan; Qingliang Zeng; Xin Zhang; Kuidong Gao (Advances in Materials Science and Engineering)
In order to overcome conical pick wear in the traditional rock cutting method, a new cutting method was proposed on account of increasing free surface of the rock. The mechanical model of rock plate bending under concentrated force was established, and the first fracture position was given. The comparison between experimental and numerical results indicated that the numerical method is effective. A computer code LS-DYNA (3D) was employed to study the cutting performance of a conical pick. To study the rock size influenced on the cutting performance, the numerical simulations with different thickness, width, and height of a rock plate was carried out. The numerical simulation with the different cutting parameters of cutting speed, cutting angle, and cutting position influenced on cutting performance was also carried out. The numerical results indicated that the peak force increased with the increasing thickness of rock plate. With the increasing width and height of the rock plate, the peak force decreased and then became stable. Besides, the peak force decreased with the increasing of cutting position lxp/lx. Moreover, the peak force increased and then decreased with the increasing of cutting angle. The cutting speed has nonsignificant influence on the peak force. The strong exponential relationship was obtained between the peak force and cutting position, thickness, height, and width of the rock plate at a confidence level of 0.95. A binomial relationship was observed between the peak force and cutting angel. The cutting force comparison between traditional rock cutting and rock plate cutting indicated that the new cutting method can effectively reduce peak cutting force.